THE ISOSTATIC COMPENSATION OF THE AZORES PLATEAU: A 3D ADMITTANCE AND COHERENCE ANALYSIS - Luis J.F.; Neves M.C. (My University, 2006)
The compensation of the Azores Plateau is re-examined by means of a 3D admittance study involving computations of the admittance between the bathymetry and (1) the geoid, (2) the free air gravity and (3) the mantle Bouguer anomalies. The geoid to bathymetry relationship, rather than being analysed in the space domain, is studied in the spectral domain. In this way, the information related to the flexural response of the lithosphere is retained in the geoid to bathymetry signal and can be compared to that of the gravity to bathymetry. We find that the anomalously shallow depths of the Azores Plateau are not due to dynamic forces sustained by mantle upwelling. The Plateau is supported by a thickened crust, which mainly results from large volumes of accreted extrusives and consequent deflection of the underlying elastic plate. Both the free air gravity and the mantle Bouguer admittance point to a flexural isostatic model with a Moho depth of 12 km and an elastic thickness in the range of 3-6 km. However, the analysis of the coherency between bathymetry and the mantle Bouguer anomaly indicates that buoyant material at the base of the crust partially accounts for the uplift of the Plateau. In our best-fitting model, the average elastic thickness is 4 km and the amplitude of the buoyant load at the Moho is 1 / 3 of that of the surface volcanic load. Buoyancy forces at the Moho may arise from underplated material resulting from subcrustal plutonism. © 2006.
Keywords: ADMITTANCE; AZORES SWELL; GEOID INTERPRETATION; GRAVITY; ISOSTASY